Managing the world economy - Mills, John (Palgrave Macmillan, 2000)
Mills is an economist who has spent his career running companies engaged in making and selling consumer goods. He argues that while much has been achieved since the beginning of the Industrial Revolution, more appropriate policies could have produced much higher economic growth and a more effective use of human resources without undue risk of inflation. He suggests policies to improve the economy, especially of the western industrialized countries, which have been groaning most miserably under slow growth and high unemployment for a quarter of a century.